Acting, thinking, feeling, making, collaborating: The engagement process in foreign language learning. (November 2019) - Oga-Baldwin, W.L. Quint
Abstract: Engagement represents the goal most teachers seek when imagining the ideal classroom. When teachers speak of motivating their students, they refer to getting them on task, inducing them to pay attention, helping them complete assignments, and stimulating them towards asking probing questions. All the while, students feel relaxed, energized, joyous in their learning. Numerous theoretical frameworks have been tied to engagement, indicating its importance as a construct beyond any one single paradigm. Some models treat engagement as an outcome, others a dynamic pivot in the motivational process, and reciprocally related to student and teacher interactions. The topic has wide coverage in first language studies, and has been a topic of growing interest in education and educational psychology, but has had only limited adoption as a topic of study in language education. As a construct more easily recognizable to teachers, discussing engagement may help bridge the "black box" world of the classroom, the "impractical" world of educational theory, and the "uninformed" perspective of lay theorists. The current review covers the basic theoretical and methodological issues in measuring and using engagement as a construct for understanding second and foreign language learning in classrooms.